Diagnostic errors in neonatology - T.K. Mavropulo; O.O. Vlasov; O.Yu. Vereshchak (Zaslavsky O.Yu., 2022)
Background. Тhe incidence of diagnostic errors in neonatology and their impact on children's health remain relatively unknown. The limited available evidence, however, suggests that diagnostic errors in the neonatal unit result in significant and long-term consequences. The purpose of the study was to generalize the literature data on diagnostic errors in neonatal units in view of their prevalence, impact on health status, and contributing factors. Materials and methods. The search was done in the PubMed Central® database using the keywords "misdiagnosis", "diagnostic errors", "neonatal intensive care unit", "neonatal unit", "neonatology", "newborns". Results. Methods to identify diagnostic errors were analyzed: autopsy results, consideration of complaints and conflicts, voluntary survey of doctors and patients, symptom-disease pair (SPADE approach), trigger methodology, Safer Dx Instrument (measurement and improvement of diagnostic safety). The incidence of detecting diagnosis errors ranged from 19.2 % when analyzing pathology studies (including 3.7 % of those that harmed a patient) to 6.2 % when using Safer Dx Instrument (including 8.0 % of those that that harmed a patient). A real assessment of this situation can be provided by a combination of the above methods. Conclusions. Further research is needed to better quantify misdiagnosis in neonatal intensive care units and to identify potential strategies to reduce its incidence or mitigate the harm associated with misdiagnosis.